Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan PT. Ramayana Lestari Sentosa Tbk Ciputat Kota Tangerang Selatan - Nazwa, Laisa An; Darzimal, Ilham Daniswara; Faradila, Syabilla; Alvahrezi, Varel; Azzahra, Veira Veronia (Jurnal Disrupsi Bisnis, 2024)
The purpose of this study was to determine the influence of leadership style and work motivation on employee performance at PT. Ramayana, Teras Kota Tangerang Selatan branch. The method used in this research is quantitative method with a population and a sample of 60 employees. Data analysis in this study includes validity test, reliability test, correlation, multiple regression analysis, coefficient of determination, classical assumption test and hypothesis testing. The results of the study partially leadership affect employee performance while work motivation has no effect on employee performance. Simultaneously, the leadership style and work motivation are tested on employee performance. This can be seen from the results of the F test, the value of Fcount> Ftable: 43.390> 3.09 and a significant value of 0.000 <0.05.